PARASITIC NEMATODE INFECTION IN THE SOUTH AMERICAN RED-FOOTED TORTOISE GEOCHELONE CARBONARIA FROM UPATA, BOLIVAR, VENEZUELA - Pérez Mata, Arlett (2014)
Geochelone carbonaria is one of the two species of tortoises that have been described in Venezuela. We report herein a severe parasitic infection with strongylid and pinworm nematodes in 15 red-footed tortoises, G. carbonaria from Upata, State of Bolivar, Venezuela. Animals were obtained from the owner of a cattle ranch in the savannah and allocated in a restricted area. Two months later, animals became ill, displaying anorexia, lethargy and diarrhea. Faeces were fluid, mucoid and haemorragic. Five animals were found dead. At necropsy, caecum and colon were enlarged due to the presence of hundreds of small nematode parasites in their lumen; mucosal haemorragy and fibrin tracts in the liver were also observed. Faecal samples and part of the intestinal content were analyzed in the laboratory. Faecal examination showed a severe strongylid and pinworm infection. Intestinal content was abundantly infected by pinworm nematodes identified, at genus level, as Atractis (Order Ascaridida: Cosmocercoidea), and Thelandros (Order Oxyurida: Pharyngodonidae). This represents the first report of both genera in G. carbonaria in Venezuela. Animals were orally treated with Albendazole (10 mg·kg-1), once a day for three days. Nematodes were expelled and health condition of the animals improved dramatically. Stress is a common cause of outbreak of parasitism in recently captured reptiles.